The Effectiveness of Musical Accompaniment as a Medium for Vocal Instruction at Hafid Vocal Academy - Asmarani, Kidung Sukma; Bahtiar, Hafid Zuhdan (Jurnal Seni Musik, 2025)
This study aims to determine the effectiveness of using musical accompaniment as a medium for vocal instruction at Hafid Vocal Academy. The data were collected using a qualitative case study approach, employing several techniques including observation, interviews with vocal instructors, and documentation of learning activities. Data analysis was conducted through data reduction,  presentation, and conclusion drawing. The validity of data was strengthened through triangulation techniques. The study's findings show that using musical accompaniment as a medium for vocal instruction at Hafid Vocal Academy has proven effective in enhancing several aspects. Based on the findings, these aspects include: first, increased student motivation and enthusiasm in participating in the lessons; second, improved vocal technique; third, enhanced expression and song interpretation through musical accompaniment; and finally, increased student engagement in the learning process.